Green Architecture Concepts Applied to Wanakota Apartments - Andiyan Andiyan; Abdul Gani Alfarizi (Tesa Arsitektur, 2021)
The shrinking land in urban areas and the worsening world climate crisis have created a new residential development problem. One way to maximize land designated for residential use is to build vertical housing, such as constructing flats and apartments that can accommodate more residents in a limited area. However, it also creates new problems because the use of energy required for a building will be extensive. The application of Green Architecture is an effort to reduce energy use for buildings and reduce the negative impact of buildings on the environment. one helpful reference is applying green architectural concepts. The apartment Wanakota is designed using the green building concept with the Indonesian Green Building Council (GBCI). Wanaka means City Forest, and trees inspire this name as trees. This tree is not only an aesthetic enhancer but as a CO2 absorber and oxygen supplier in the environment.